Mechanism‐based inhibition of HsaD: a C‐C bond hydrolase essential for survival of Mycobacterium tuberculosis in macrophage. Issue 1 (6th November 2013) - Ryan, Ali; Keany, Sebastian; Eleftheriadou, Olga; Ballet, Romain; Cheng, Hung‐Yuan; Sim, Edith
Abstract Mycobacterium tuberculosis remains the leading cause of death by a bacterial pathogen worldwide. Increasing prevalence of multidrug‐resistant organisms means prioritizing identification of targets for antituberculars. 2‐hydroxy‐6‐oxo‐6‐phenylhexa‐2, 4‐dienoate hydrolase (HsaD), part of the cholesterol metabolism operon, is vital for survival within macrophage. The C‐C bond hydrolase, HsaD, has a serine protease‐like catalytic triad. We tested a range of serine protease and esterase inhibitors for their effects on HsaD activity. As well as providing a potential starting point for drug development, the data provides evidence for the mechanism of C‐C bond hydrolysis. This screen also provides a route to initiate development of fragment‐based inhibitors.